Progress in coherent lithography using table-top extreme ultraviolet lasers - Li, Wei, author; Marconi, Mario C., advisor; Menoni, Carmen S., advisor; Wu, Mingzhong, committee member; Krapf, Diego, committee member (Colorado State University. Libraries, 2016)
Nanotechnology has drawn a wide variety of attention as interesting phenomena occurs when the dimension of the structures is in the nanometer scale. The particular characteristics of nanoscale structures had enabled new applications in different fields in science and technology. Our capability to fabricate these nanostructures routinely for sure will impact the advancement of nanoscience. Apart from the high volume manufacturing in semiconductor industry, a small-scale but reliable nanofabrication tool can dramatically help the research in the field of nanotechnology. This dissertation describes alternative extreme ultraviolet (EUV) lithography techniques which combine table-top EUV laser and various cost-effective imaging strategies. For each technique, numerical simulations, system design, experiment result and its analysis will be presented. In chapter II, a brief review of the main characteristics of table-top EUV lasers will be addressed concentrating on its high power and large coherence radius that enable the lithography application described herein. The development of a Talbot EUV lithography system which is capable of printing 50nm half pitch nanopatterns will be illustrated in chapter III. A detailed discussion of its resolution limit will be presented followed by the development of X-Y-Z positioning stage, the fabrication protocol for diffractive EUV mask, and the pattern transfer using self- developed ion beam etching, and the dose control unit. In addition, this dissertation demonstrated the capability to fabricate functional periodic nanostructures using Talbot EUV lithography. After that, resolution enhancement techniques like multiple exposure, displacement Talbot EUV lithography, fractional Talbot EUV lithography, and Talbot lithography using 18.9nm amplified spontaneous emission laser will be demonstrated. Chapter IV will describe a hybrid EUV lithography which combines the Talbot imaging and interference lithography rendering a high resolution interference pattern whose lattice is modified by a custom designed Talbot mask. In other words, this method enables filling the arbitrary Talbot cell with ultra-fine interference nanofeatures. Detailed optics modeling, system design and experiment results using He-Ne laser and table top EUV laser are included. The last part of chapter IV will analyze its exclusive advantages over traditional Talbot or interference lithography.
Keywords: interference; nanofabrication; Talbot; metasurface; EUV; soft X-ray laser